A large eagle (Aves, Accipitridae) from the early Miocene of Panama. (14th September 2016) - Steadman, David. W.; MacFadden, Bruce J.
Abstract: We report the first Tertiary bird fossil from Central America, an ungual phalanx from a large, unknown genus and species of Accipitridae from the early Miocene Centenario Fauna, Panama. This specimen provides another example of a Neogene bird from North and Central America with its possible closest living relatives occurring today in Africa. In contrast, there is no evidence of African affinities among the reptile or mammal fossils from the Centenario Fauna.